Seleção de linhagens de feijão rajado para múltiplos caracteres agronômicos, de qualidade de grãos e minerais - Argenta, Henrique da Silva (2024)
The development of cranberry bean lines has increased due to their export potential, but only lines that have high agronomic performance and grain quality has been registered as cultivars, requiring the characterization and simultaneous selection of multiple traits of interest. The objectives of this work were: (1) to evaluate whether cranberry bean lines differ for agronomic, technological quality, and mineral traits; (2) to analyze the efficiency of indirect selection by decomposing the correlations between agronomic traits and grain productivity, and between technological and mineral traits and grain cooking time; and (3) select cranberry bean lines for multiple traits that confer high agronomic performance and for high grain quality and mineral concentration. For this, three experiments were conducted in Santa Maria, RS, in the experimental area of the Department of Plant Science at the Federal University of Santa Maria, during the 2022 rainy, 2023 dry, and 2023 rainy growing seasons. A randomized complete block design was used, with three replications. The treatments consisted of 13 cranberry common bean genotypes: 10 lines and three cultivars. In total, 38 traits were evaluated (18 agronomic, 12 technological and eight mineral). The statistical analyses employed were individual analysis of variance, joint analysis of variance, Scott–Knott cluster test, multicollinearity diagnosis, path analysis and selection indices (sum of ranks and multiplicative). The genotypes showed variability for almost all traits and significant genotype × environment interaction for most. The number of pods per plant (0.62) and the height of insertion of the first pod (-0.58) were the traits with the greatest direct effect on grain yield. Phosphorus concentration had the greatest direct effect (-0.69) with cooking time. The sum of ranks index allowed simultaneous gains for all agronomic traits and selected the genotypes CNFRJ 17545, BRS FS311, and CNFRJ 17792. These genotypes have a lower incidence of common bacterial blight, upright plant architecture, and higher grain yield. The application of the multiplicative index resulted in favorable gains for most technological traits and all mineral concentration, except for chroma value. The lines CNFRJ 17774, CNFRJ 18239, and CNFRJ 17792 were selected by this index and show high mass of 100 grains, fast cooking time, and higher concentrations of potassium, phosphorus, iron, copper, and manganese in the grains.